Association of HIV Infection and Antiretroviral Therapy With Arterial Stiffness: A Systematic Review and Meta-Analysis. Issue 2 (August 2021) - Kuate Defo, Alvin; Chalati, Mhd Diaa; Labos, Christopher; Fellows, Lesley K.; Mayo, Nancy E.; Daskalopoulou, Stella S.
Abstract : Incidence of cardiovascular disease in people living with HIV has increased as overall survival has improved because of combination antiretroviral therapy (cART). Arterial stiffness is a composite indicator of cardiovascular disease risk independent of traditional risk factors. We aimed to synthesize the evidence on the relation of HIV and of cART to arterial stiffness. Medline, Embase, CINAHL, PubMed, and Cochrane Libraries were systematically searched for studies relating HIV/cART to arterial stiffness until June 2019. A standardized extraction form was used to collect data from published reports. Random-effects meta-analyses were performed to produce standardized mean differences and 95% CIs from studies reporting carotid-femoral pulse wave velocity. We retrieved 995 citations. Seventy-four studies (N=18 711 participants/13 119 with HIV) were included: 59 cross-sectional, 9 cohort, and 6 randomized trials. In meta-analyses of 17 studies, arterial stiffness was found to be elevated overall in individuals with HIV relative to controls (standardized mean difference, 0.44 m/s [95% CI, 0.25–0.63]) and in cART-treated versus untreated individuals with HIV (standardized mean difference, 0.35 m/s [95% CI, 0.13–0.57]). Several studies suggested that cumulative exposure to cART is associated with a continual increase in arterial stiffness. However, early initiation of treatment might improve arterial stiffness later in life. The results highlight the need for monitoring of cardiovascular risk in this population. The cross-sectional nature of most studies (59/74) mainly allowed for the exploration of associations; large longitudinal studies are needed to confirm the observed associations and establish causality between HIV/cART and arterial stiffness. Abstract : Supplemental Digital Content is available in the text.